Influence of Colchicine Treatments on Character Expression and Yield Traits in Cowpea (Vigna Unguiculata L. Walp) (Global Journal of Science Frontier Research, 2014)
Mutagenesis has been exploited to enhance genetic variability in cowpea (Vigna unquiculata L. Walp.); an important legume in the tropical and subtropical regions of the world. Mutation is regarded to be a shortcut breeding technique, which has produced new and high yielding varieties through heritable changes in genetic constitution of characters in some leguminous crops. Effects of 0.1% aqueous solution of colchicine for different periods of time, viz; -0, 2, 4 and 6 hours were tested on the quantitative and yield characters of a cowpea variety popularly known as 'Oloyin' in M1 generation. Lethal dose value (LD40) of 59% was observed at 2 hours treatment. Treatment was significant (P = 0.05) for seedling emergence percentage (67 -13%), plant height (21.52 -15.63 cm), number of leaves (11.08 -4.98), number of nodes on main stem (6.26 -4.5), survival percentage (63.50 -12.50%) and number of days to first flowering (55.52 -47.30) while treatment was not significant for all other characters studied.
Keywords: mutagenesis; genetic variability; induced variation